Pathology of Parental Involvement in Their Children’s Enrollment in Preschools: A Case Study of Neyriz - Aref, Khadijeh; Vares, Mehdi (American Journal of Humanities and Social Sciences, 2016)
The objective of this study was to identify the pathology of parental involvement in their children’s enrollment in preschools of Neyriz. The study used the survey questionnaire to meet the research objectives. The study population were parents who had preschoolers which, for the purpose of the study, 217 sample were chosen via Morgan formula. The data collection instrument was self-made questionnaire based on 5-point Likert scale. Next, the data were analyzed using descriptive statistics. One sample t-test, and Friedman test were used to determine if significant influence exist between the variables. The findings showed that economic, social individual and educational factors have a significant influence on parental involvement in their children’s enrollment. However, Friedman test results indicated that, among those variables, the educational factor has most influence on parental involvement. It is recommended that educational institutions pay more attention to the educational and economic factors and provide free education towards increasing children’s enrollment in preschools.